Impact of Perceived Usefulness on Actual Chatbot System Usage: An Attitude Toward Using Mediation Approach on Shopee E-commerce - Muhammad Nauval Daffa Agresdiant; Ratih Amelia (Jurnal Informatika Ekonomi Bisnis, 2026)
The rapid growth of e-commerce in Indonesia, driven by internet penetration reaching 229.4 million users in 2025, has intensified marketplace competition with Shopee maintaining its dominant position. While chatbot AI has become a critical customer service interface in e-commerce platforms, its mere presence does not guarantee actual use by all users. This study aims to examine the influence of Perceived Usefulness on Actual System Usage of Shopee's chatbot, with Attitude Toward Using as a mediating variable, within the Technology Acceptance Model framework. A quantitative explanatory approach was employed, involving 190 Shopee chatbot users in East Java selected through purposive sampling. Data were collected via an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling with SmartPLS 3, including bootstrapping with 5,000 resamples for mediation testing. All four hypotheses were supported. PU significantly influences ATU (β = 0.623; p < 0.001) and ASU directly (β = 0.265; p = 0.003). ATU significantly influences ASU (β = 0.540; p < 0.001). ATU partially mediates the PU–ASU relationship with an indirect effect of 0.336 and VAF of 55.9%, confirming complementary partial mediation. The model explains 54.0% of ASU variance. ATU serves as the dominant mediating mechanism through which PU influences actual chatbot usage, with more than half of PU's total effect on ASU operating through positive attitude formation. These findings underscore the strategic importance of affective user experience design alongside functional improvements in e-commerce chatbot development.